A Latent Markov Model with Covariates to Study Unobserved Heterogeneity among Fertility Patterns of Couples Employing Natural Family Planning Methods - Pennoni, Fulvia; Barbato, Michele; Del Zoppo, Serena (Frontiers in Public Health, 2017)
Purpose We use the historical data from the European Study of Daily Fecundability and we develop an algorithm to determine the fertile window in a woman’s cycle according to the rules of the C.A.Me.N. symptothermal method proposed by the Centro Ambrosiano Metodi Naturali. Our aim is to identify variables acting on the probability of conception by considering the fertile window and factors that cannot be explained by employing the observed covariates of individuals and couples. Methods We adopt the latent Markov model with covariates tailored for data collected at times when a latent process detects the dependence across fertile periods of each woman’s cycle. We consider measurement errors, transitions between conception and non-conception, and the prediction of conception rate over the fertile windows. Conclusion We find that the conception pattern is mainly related to sexual intercourse behavior during the fertile window and to previous pregnancies. For the cohort under study, we predict a steep decline in the average conception rate across fertile windows.